FINANCIAL ASPECTS OF EDUCATION QUALITY ASSURANCE IN LATVIA - Iryna Kalenyuk; Olga Verdenhofa; Lyudmyla Tsymbal (Izdevnieciba "Baltija Publishing", 2018)
The article analyzes the financial aspects of ensuring the quality of higher education, the relevance of which is due to the increasing importance of higher education in the development of countries in the modern conditions. The importance of ensuring and maintaining the quality of higher education for each country is proven. On the basis of historical and comparative research methods, a consistent process of formation of the quality assurance system of higher education in Latvia was characterized. The complexity of the problem of improving the quality of education, which is ensured not only by accreditation system, but also financial aspects, is confirmed: increase of financial autonomy of higher educational establishments, expansion of resource base, increase of financing volumes. The features of the financing mechanism of institutions of higher education are revealed, the strengths and weaknesses of the system of financing higher education of Latvia in comparison with European countries are analyzed. The positive experience of European and other countries in the formation of effective financing mechanisms that can influence the quality of higher education is presented. The analysis allowed to determine the perspective directions of development of the Latvian system of higher education in the conditions of the modern global environment and to formulate proposals for improving the mechanisms of its financing. The necessity of improvement of the Latvian practice in the direction of strengthening of stimulating character, further diversification of sources and formation of the practice of financing, oriented on efficiency is proved. Special attention is needed to increase the amount of funding and to bring its indicators to average European indicators, increasing attention to financing research through domestic resources (public, private, business, etc.).